Evaluation of the Effect of Chia (Salvia hispanica) Seeds Extract in modulating Fertility Potential, Injury and Histopathological Alterations Induced by Fenitrothion in Male Rats - Abed Mohammed, Sameer; M Al Yassen, Ahmed; Salim Ali, Marwa; Flayyih Hasan, Ahmed; M El Wahsh, Hany; Korish, Mohamed (The Indian Journal of Animal Reproduction, 2025)
The study aimed to evaluate the effect of chia seed extract as a protective against fenitrothion toxicity in male rats. Total  forty rats were divided into four groups: the first group was the control group (no treatment), the second group was  treated with Chia (Salvia hispanica) seeds at a dose of 400 mg/kg body weight daily, the third group was treated with  Fenitrothion at a dose of 100 mg/kg body weight, and the fourth group was treated with both Chia (Salvia hispanica)  seeds and fenitrothion. Rats were treated orally for three weeks daily. The results showed changes in the concentration  of hormones and sperm characteristics in rats treated with fenitrothion compared to the control group. The exposure to  fenitrothion has a noticeable toxic effect on rats through measuring some vital indicators. The role of chia seed extract  in reducing lipid oxidation and improving the antioxidant defense system has been proven. We conclude from the above  that exposure to fenitrothion has a noticeable toxic effect on rats through measuring some vital indicators, The role of  chia seed extract in reducing lipid oxidation and improving the antioxidant defense system has been proven
Keywords: Chia (Salvia hispanica) seeds extract; FSH; Fenitrothion; LH; Testosterone; Sperm count; Rat